Analisis Postur Kerja dengan Metode Rapid Entire Body Assessment (REBA) pada Operator Shift Kerja 1 di Machine Shop PT. XYZ - Yudi, Rifky Rivaldo Putra; Sarungu, Selvia; Sugeng, Bambang (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. XYZ is one of the companies that has a machine shop department which is an environment where machinery and a form of subtractive manufacturing are carried out. Machine operator workers do their work for 8 hours per day with 2 breaks and less muscle stretching during their work activities. These activities cause operators to experience complaints of fatigue, discomfort, aches and pains in several parts of the body which can cause the risk of musculoskeletal disorders (MSDs). Based on these problems, an analysis of work posture was carried out using the Rapid Entire Body Assessment (REBA) method because it can assess the risk to all parts of the body. This study was conducted on the activities of grinding and inspection operators. Based on the results of the study with the calculation of the REBA score, it is known that the activities of the grinding operator got a score of 10, and the inspection operator got a score of 9, each of which has a high risk level and requires improvement. Proposals for improving the work posture of operators with recommendations for chair and table aids.